Microscopic origin of electric-field-induced modulation of Curie temperature in cobalt. (6th June 2018) - Ando, Fuyuki; Yamada, Kihiro T.; Koyama, Tomohiro; Ishibashi, Mio; Shiota, Yoichi; Moriyama, Takahiro; Chiba, Daichi; Ono, Teruo
Abstract: The Curie temperature T C is one of the most fundamental physical properties of ferromagnetic materials and can be described by the Weiss molecular field theory with the exchange interaction of neighboring atoms. Here, we demonstrate the electrical control of exchange coupling in cobalt films through direct magnetization measurements. We find that the reduction in magnetization with temperature, which is caused by thermal spin wave excitation and scales with Bloch's law, clearly depends on the applied electric field. Furthermore, we confirm that the correlation between the electric-field-induced modulation of T C and that of exchange coupling follows the Weiss molecular field theory.